Contiendas discursivas, contiendas doctrinales. La inserción de fragmentos del discurso litúrgico en La fazienda de Ultramar. - LAURA MARTI, MELISA (Scripta Mediaevalia, 2023)
La fazienda de Ultramar is a thirteenth-century text in which it is possible to recognise several hypotexts: apocryphal stories, historical accounts, and a mythological tale are structured by the descriptive narrative frame of medieval pilgrim guides or itineraria, which gives this early Castilian translation of the Bible a distinctive form. We will focus on one of these hypotexts: the Latin quotes that accompany and expand many biblical passages, which reveal the presence and influence of liturgical texts in the study of the Bible. Through the analysis of the interaction of these two sources (the Bible and liturgical chants), we will approach the translation process of this work, as well as its doctrinal background, hoping it will allow us to comprehend the cultural system its author inhabited and the techniques he incorporated as a translator and a compiler.